2019
DOI: 10.1007/s00428-019-02527-7
|View full text |Cite
|
Sign up to set email alerts
|

AL amyloidosis with a localized B cell neoplasia

Abstract: Immunoglobulin light chain-derived (AL) amyloidosis may occur as a systemic disease usually with dismal prognosis and a localized variant with favorable outcome. We report 29 patients with AL amyloidosis and associated lymphoplasmacytic infiltrate spatially related to amyloid deposits. In 17 cases, the amyloid deposits were classified as ALλ and 12 as ALκ Histopathology in all cases showed relatively sparse plasma cells and B cells without tumor or sheet formation by the lymphoplasmacytic infiltrate. The B cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…29 to detect the clone in most cases, while more sophisticated approaches for clonality assessment, for example, in situ hybridization and molecular pathological analyses, are more effective. 5,11,13 Since these latter techniques were not systematically used in our study, it is possible that we identified only cases with more extended B-cell clones, while cases with more subtle infiltrations could have been missed for example, due to sampling errors (note the correlation with sample size) or technical issue…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 to detect the clone in most cases, while more sophisticated approaches for clonality assessment, for example, in situ hybridization and molecular pathological analyses, are more effective. 5,11,13 Since these latter techniques were not systematically used in our study, it is possible that we identified only cases with more extended B-cell clones, while cases with more subtle infiltrations could have been missed for example, due to sampling errors (note the correlation with sample size) or technical issue…”
Section: Discussionmentioning
confidence: 99%
“…However, a larger study revealed that the infiltrate is currently best classified as "localized B-cell neoplasia of undermined significance" in the majority of cases. 13 Thus, like in sysAL, the amyloidogenic clone is usually small and has not the full characteristics of a well-defined malignant disease. 4 The B-cell clones in locAL might have other not yet known biologic characteristics that affect the outcome, as already observed in sysAL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the preceding decades, we and others have collected ample evidence of the tissue-specific patterns from different types of amyloid deposits (Mahmood et al 2015;Freudenthaler et al 2016;Baumgart et al 2018;Stuhlmann-Laeisz et al 2019). Hence, we consider amyloidosis as a disease of cells and tissues, and amyloid itself as a "gemisch" (mixture) of constituents that show organ-, tissue-, and amyloid-type specific patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few, small case series reported an association between marginal zone lymphoma (MZL) of mucosaassociated lymphoid tissue and localized AL amyloidosis, mainly with nodular pulmonary involvement. [17][18][19] Recently, German investigators published a series of 29 patients with AL amyloidosis and localized B-cell neoplasia, mostly with an MZL immunophenotype 20 ; only 5 patients had systemic lymphoma, and 2 were classified as systemic AL amyloidosis.…”
mentioning
confidence: 99%